2020
DOI: 10.1109/access.2020.2974792
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Aerial Combat Game via Optimization-Based Receding Horizon Control

Abstract: This paper focuses on modeling of air-to-air combat via optimization-based control and gametheoretic approach. The flatness property of the dynamical system is used to present aircraft dynamics in terms of specific variables and their derivatives that can be described via a set of parameterized curves. With the help of game theory, the combat between two aircraft is translated into an optimization problem in terms of these parameterized curves. The optimization problem is solved with a moving time horizon sche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 18 publications
(29 reference statements)
0
14
0
Order By: Relevance
“…The work of Başpınar, Barış et al [ 81 ] focuses on the modelling of air-to-air combat between two unmanned aerial vehicles (UAVs) using an optimization-based control and game-theoretic approach. In this work, vehicle motion is expressed in terms of specific variables and any trajectory planning for moving from one waypoint to another is solved by determining the smooth curves satisfying defined conditions in flat output space.…”
Section: Use Of Game Theory In Defence Science and Technology Applica...mentioning
confidence: 99%
See 1 more Smart Citation
“…The work of Başpınar, Barış et al [ 81 ] focuses on the modelling of air-to-air combat between two unmanned aerial vehicles (UAVs) using an optimization-based control and game-theoretic approach. In this work, vehicle motion is expressed in terms of specific variables and any trajectory planning for moving from one waypoint to another is solved by determining the smooth curves satisfying defined conditions in flat output space.…”
Section: Use Of Game Theory In Defence Science and Technology Applica...mentioning
confidence: 99%
“…In [ 81 ], the authors provide cost functions associated with the degree of being in tail-chase to the target based on aspect and bearing angles as well as the cost functions associated with generating a maximum score when the opponent is within some threshold of the optimum shooting range. The cost functions are multiplied together to create the total cost.…”
Section: Use Of Game Theory In Defence Science and Technology Applica...mentioning
confidence: 99%
“…Several algorithms and approaches have been applied to realize control systems that enable autonomous systems to execute complex missions [29][30][31][32][33][34][35]. For instance, an autonomous decision-making for unmanned combat aerial vehicles (UCAVs) using genetic fuzzy trees is presented by authors in [29].…”
Section: Related Workmentioning
confidence: 99%
“…A multi-agent-based training system for USVs was presented in [35] and a combat task for combat USVs was used to evaluate the system performance. Other methods such as optimizations and game theoretic approaches have been reported [31][32][33].…”
Section: Related Workmentioning
confidence: 99%
“…Zain et al suggested that SQP is an efficient way to solve the power allocation problem in PD-NOMA with the min-max objective function [14]. The SLSQP is a SQP algorithm that uses an equivalent least-squares problem formulation and is considered as a popular method to implement SQP [39], [40], [41] This section uses box-plots to show the results. Therefore, we provide a short note on comprehending the box plots as follows: (i) The lines in the middle of the boxes show the median of a data series; (ii) The lower and upper edges of the rectangle represent the Q1 and Q3 percentile of a data-series; (iii) The whiskers are small horizontal lines.…”
Section: Simulationsmentioning
confidence: 99%